2018
DOI: 10.1159/000487760
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Hypomagnesemia and Pulmonary Function Tests in Patients with Chronic Asthma

Abstract: Objective: To investigate the relationship between serum values of magnesium and the parameters of the pulmonary function tests (PFT) in patients with chronic asthma. Subjects and Methods: This study recruited 50 patients with chronic stable asthma and 40 healthy individuals as a control group. Data on age, sex, severity of asthma, PFT, and details of drug therapy were obtained from each group. Serum magnesium, potassium, phosphorus, calcium, and sodium levels were also measured. To evaluate differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The role of magnesium in asthma is not clear, although many studies have found hypomagnesemia in chronic stable asthmatics as well as during asthma exacerbations [32,33,34].…”
Section: Cardiovascular Manifestationsmentioning
confidence: 99%
“…The role of magnesium in asthma is not clear, although many studies have found hypomagnesemia in chronic stable asthmatics as well as during asthma exacerbations [32,33,34].…”
Section: Cardiovascular Manifestationsmentioning
confidence: 99%
“…5 In a study done by Fantidis P et al which measured polymorphonuclear magnesium content in patients with asthma, low polymorphonuclear magnesium content was seen in patients with bronchial asthma. 6 In a study by Kilic et al 7 and OS Alamoudi 8 , hypomagnesemia and hypophosphatemia were found to be the most common electrolyte abnormalities in patients with chronic stable asthma. There is no popular marker for association with level of control of asthma.…”
Section: Discussionmentioning
confidence: 96%
“…Anxiety and Depression among Adolescents control. It was serum magnesium, 2,3 erythrocytic magnesium, 4,5 polymorphonuclear magnesium, 6 hypomagnesemia and hypophosphatemia 7,8 in different studies.…”
Section: Original Articlementioning
confidence: 91%
See 1 more Smart Citation
“…This may be related to respiratory muscle weakness caused by hypomagnesemia (10) . In addition, magnesium regulates the contractibility of smooth muscle cells, and hypomagnesemia leads to bronchospasm, which in turn prolongs mechanical ventilation (11) . Our study found that the duration of vasoactive drug use in patients with hypomagnesemia was longer than that in patients without hypomagnesemia, however, the pathological mechanism remained unclear.…”
Section: Discussionmentioning
confidence: 99%